2012
DOI: 10.1038/onc.2012.171
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β and NF-κB signal pathway cross-talk is mediated through TAK1 and SMAD7 in a subset of head and neck cancers

Abstract: TGF-β plays a dual role in epithelial malignancies, including head and neck squamous cell carcinoma (HNSCC). Attenuation of canonical TGF-β signaling enhances de novo tumor development, while TGF-β overexpression and signaling paradoxically promotes malignant progression. We recently observed that TGF-β-induced growth arrest response is attenuated, in association with aberrant activation of Nuclear Factor-κB (NF-κB), a transcription factor which promotes malignant progression in HNSCC. However, what role cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
202
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(211 citation statements)
references
References 58 publications
8
202
0
1
Order By: Relevance
“…On the basis of these data, it has been suggested that in the context of ovarian cancer, mutations and/or alterations of the key nodes along canonical TGF-b pathway shift TGF-b to noncanonical pathways such as activation of NF-kB which describes the pro-oncogenic role of TGF-b in advanced ovarian cancer (38,39). In fact, activation of TGF-b/NFkB pathway has been defined as the underlying mechanism in the phenomenon of conversion of TGF-b from a tumor suppressor to a tumor promoter during tumorigenesis (28,40,41). In our study, it was found that minocycline downregulates the endogenous levels of TGF-b1.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these data, it has been suggested that in the context of ovarian cancer, mutations and/or alterations of the key nodes along canonical TGF-b pathway shift TGF-b to noncanonical pathways such as activation of NF-kB which describes the pro-oncogenic role of TGF-b in advanced ovarian cancer (38,39). In fact, activation of TGF-b/NFkB pathway has been defined as the underlying mechanism in the phenomenon of conversion of TGF-b from a tumor suppressor to a tumor promoter during tumorigenesis (28,40,41). In our study, it was found that minocycline downregulates the endogenous levels of TGF-b1.…”
Section: Discussionmentioning
confidence: 99%
“…46 Numerous reports underlined that through TGFb secretion MSC promote a malignant phenotype in tumor cells of different histotype 10,21 The higher level of TGFb secreted by acidic MSC does not prevent proliferation of LpH-MSC-adapted melanoma cells, a condition that might be related to SMAD/NF-kB signaling interplays, as suggested by Freudlsperger et al's findings in head and neck cancers. 32 We also found that esomeprazole, a proton pump inhibitor activated by acidic medium, inhibits TGFb of acidic MSC, which corresponds to a MET program in melanoma cells grown in LpH-esomeprazole-treated MSC medium. These cells were characterized by a reduction of N-cadherin, TGFb, invasiveness and motility, and elevation of E-cadherin.…”
Section: Discussionmentioning
confidence: 90%
“…28 NF-kB and melanoma progression is reviewed by Amiri and Richmond. 29 Elevation of NF-kB expression in melanoma cells grown in LpH-MSC medium is potentially involved in several aspects of the acquired phenotype, such as stabilization of Snail transcription factor, 30 loss of E-Cadherin expression, 31 attenuation of TGFb-induced inhibition of proliferation 32 and, finally, metabolism. 33 Thereafter, these cells express an increased motility and invasiveness after suspension in MMP-enriched LpH-MSC medium.…”
Section: Discussionmentioning
confidence: 99%
“…73,74 Thus, it would be interesting to test whether H 2 O 2 -induced conversion of ECs into myofibroblasts is inhibited by a p38 MAPK inhibitor; however, further experiments are needed to test this idea. Although NF-kB activity is normally suppressed by TGF-b in normal cells, NF-kB can be activated upon TGF-b treatment in pathological cells, 25,26,75,76 which could be the mechanism for H 2 O 2 -induced conversion of ECs into myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Several proteins that are involved in TGF-b intracellular signaling include the canonical pathway of phosphorylation of the family of Smad proteins and non-canonical intracellular pathways, to perform the activation of nuclear factor-kappa B (NF-kB). [24][25][26][27][28] Specifically, the Smad3 protein emerges as a pro-fibrotic member of the Smad protein family because its phosphorylation promotes the progression of fibrosis. 29,30 It has been reported that oxidative stress induces the EMT.…”
mentioning
confidence: 99%